2015
DOI: 10.5606/archrheumatol.2015.4675
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 as a Biomarker of Subclinical Lupus Nephritis

Abstract: Objectives:This study aims to investigate the relationship between serum interleukin-18 (IL-18) and its renal expression with histological classification of lupus nephritis in patients with insignificant proteinuria, and evaluate serum IL-18 as a biomarker of subclinical renal involvement in lupus patients. Patients and methods: Forty lupus patients (5 males, 35 females; mean age 26.3±7.9 years; range 16 to 52 years) with proteinuria less than 0.5 g/24 hours and 20 healthy controls (2 males, 18 females, mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Among all the mediators that are significantly associated with HLA-DRB1 * 04 alelle, IFN-γ, IL-18, VEGF and LPO warrant further investigations as these immune mediators are robustly linked to the pathogenesis of LN in SLE patients ( Table 6 ). Some studies even suggested that IL-18 ( 95 , 97 , 98 ), IFN-γ ( 81 83 ), LPO ( 100 ) and VEGF ( 108 , 109 ) could serve as host biomarkers in assessing the renal disease activity and/or discerning between SLE patients with and without lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Among all the mediators that are significantly associated with HLA-DRB1 * 04 alelle, IFN-γ, IL-18, VEGF and LPO warrant further investigations as these immune mediators are robustly linked to the pathogenesis of LN in SLE patients ( Table 6 ). Some studies even suggested that IL-18 ( 95 , 97 , 98 ), IFN-γ ( 81 83 ), LPO ( 100 ) and VEGF ( 108 , 109 ) could serve as host biomarkers in assessing the renal disease activity and/or discerning between SLE patients with and without lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…9 In comparison with healthy controls, patients with lupus presented with significantly higher IL-18 levels in serum, which reflects the severity extent of renal damage in lupus. 10,11 Recent studies have demonstrated that lpr mice administered an IL-18 DNA vaccine exhibited a significant reduction in glomerulonephritis and renal damage, 12 suggesting that inhibition of IL-18 production may be an effective therapeutic strategy for LN.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several recent studies have reported correlations between IL-18 and disease severity, organ involvement and a list of classic testing biomarkers like anti-dsDNA antibody, C3, C4 and etc 32,37 . In lupus nephritis, IL-18 is also related with proteinuria and renal activity and elevates earlier than the occurrence of proteinuria and high disease severity score, indicating that IL-18 has the chance to be used as a predictive marker to distinguish diverse stages of LN, even in subclinical stage 41 . These updated findings can help broaden the clinical applications of IL-18 and enrich its comprehensive significance in SLE.…”
Section: Discussionmentioning
confidence: 99%